Entwicklung einer Röntgenzoomlinse - Kornemann, Elisa (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2019)
Imaging methods such as X-ray microscopy are used in non-destructive material analysis to achieve resolutions in the sub micrometer range. Imaging optics are required, for which X-ray lenses are particularly suitable for photon energies above 10 keV. To ensure the universal use of these lenses with constant optical properties over a wide photon energy range, for the first time an X-ray zoom lens was developed in this work.